The Effect of Pyrolysis Temperature on the Performance of Sewage Sludge Biochar for Persulfate-based Oxidation of Bisphenol-A - Nurul Alvia Istiqomah; Thi Vinh Nguyen; Dick Dick Maulana (Journal of the Civil Engineering Forum, 2026)
Converting sewage sludge into biochar shows promise as an eco-friendly and cost-effective method for remediating pollutants. In this study, aerobic digested sewage sludge was evaluated as a low-cost carbon-based catalyst through a facile one-pot pyrolysis process. The sludge biochar (SBC) was then used as a persulfate (PS) activator for the degradation of Bisphenol-A (BPA). The effect of pyrolysis temperature on the physicochemical properties of SBC and catalytic activity was observed. Then, chemical quenching analysis was carried out to identify reactive species. Increasing the pyrolysis temperature from 350 to 700 °C resulted in an enhancement of the degradation rate constant of BPA from 0.95 × 10-2 min-1 to 8.9 × 10-2 min-1. SBC pyrolyzed at 350 °C (A350), characterized by a high iron content (40%wt) in the form of amorphous Fe (e.g., ferrihydrite) and C=C functional group promoting the radical formation which is dominated by presence of hydroxyl radicals. However, iron in an amorphous form limited the catalytic activity of A350. By contrast, non-radical pathway dominates SBC pyrolyzed at 700 °C (A700) with highest BPA removal as the result of more hydrophobic nature (lower O/C) therefore attracting more BPA and PS to the biochar surface. Graphitic structure of A700 (lower ID/IG) supports the mediated electron transfer pathway for persulfate activation. A pH range of 2–9 and the of inorganic anions (e.g., Cl-,NO3-,SO4-, and HCO3-) had negligible effects on the A700 system. This study introduces a novel approach to the value-added reuse of sewage sludge as an efficient persulfate activator for pollutant remediation with good resistance to water matrices conditions.